2010
DOI: 10.1111/j.1365-2621.2010.02308.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of biochemical properties of foam‐mat dried mango powder

Abstract: Investigations were carried out to see the impact of drying air temperature (65, 75 and 85°C) and milk as foaming agent in different concentration levels (0%, 10%, 15%, 20% and 25%) on the chemical properties of foam-mat dried mango juice powder. Chemical properties such as total sugars, ascorbic acid, total carotenes, minerals, total acid, pH, total soluble solids (TSS) and microbial load (fungal and bacterial) of foam-mat dried mango powder were determined. Data were analysed as per two-way anova, Duncan's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 19 publications
7
49
0
2
Order By: Relevance
“…The foam-mat dried mango pulp powder was prepared using the method followed by Kadam et al (2010). In brief, ripe mangoes (M. indica L.) cv.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The foam-mat dried mango pulp powder was prepared using the method followed by Kadam et al (2010). In brief, ripe mangoes (M. indica L.) cv.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have been reported for the development of mango powder using various techniques such as freeze drying, spray drying, vacuum drying, and foam-mat drying (Cano-Chauca, 2005;Harnkarnsujarit and Charoenrein, 2011;Jaya and Das, 2004;Kadam et al, 2010;Rajkumar et al, 2007;Wilson et al, 2012). The challenge in producing fruit powders is to reduce stickiness during drying and safe handling and storage of the powder (Jaya et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this method can be used to dehydrate high sugar content, heat-sensitive, sticky, and viscous food [7]. The other advantage associated with foam mat drying is the low cost operation, when compared to vacuum, freeze, and spray drying [8]. The foam mat drying method has been applied to many fruits and other food materials, such as mango pulp [9], papaya pulp [10], yogurt [11], Gac fruit aril [7], and banana [12].…”
Section: Introductionmentioning
confidence: 99%
“…Foam-mat drying is a process that helps to preserve the nutrients of the pulp for prolonged period and immediately after dehydration; in addition, the powder can be reconstituted as juice and/or used as ingredient for the preparation of beverages and food (Kadam et al, 2010) Although there is a great interest in its comprehension, drying is still one of the least understood operations, due to the complexity of the phenomena involved in the simultaneous transfer of heat, mass and amount of movement in the solid during the process (Kingsly et al, 2007). Researchers study the drying process based on the external conditions of air, relative humidity and temperature.…”
Section: Introductionmentioning
confidence: 99%